KANDUNGAN GIZI DAN INDEKS BOLU KUKUS YANG TERBUAT DARI TEPUNG UBI JALAR DAN RUMPUT LAUT - Wahidatul Ukhra Alamsyah; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Steamed sponge cake made from purple sweet potato flour and seaweed flour is an alternative food are subsituting wheat flour with purple sweet potatoes and seaweeds. The purpose of this study is to know the nutrient that contained in this steamed sponge cake and determine the glycemic index from steamed sponge cake and how the velocity raise blood sugar levels after eating the test food. This study was experimental study, namely to produce steamed sponge cake from purple sweet potato flour and seaweedwith the ratio of 50% purple sweet potato flour, 47,5 wheat flour, and 2,5% seaweed flour. Glycemic index value of steamed sponge cake made from purple sweet potato flour and seaweed flour  is analyzed by comparing the area under the curve of blood glucose response subjects The results of this study indicate that the glycemic index is based on the measurement of steamed sponge cake made purple sweet potato flour and seaweed by using a reference food such as white bread showed that the steamed sponge cake has a glycemic index value of 60 and his figure is included in the category of food that has a medium glycemic index value (55-70). The composition of nutrients in steamed sponge cake made purple sweet potato flour and seaweed are protein 11,48%, fat 4,51%, carbohydrate 49,78%, crude fiber 5,24%, and β-carotene 44,22 ppm. The energy content contained on that steamed sponge cake amounting to 285 kcal. This steamed sponge cake can be used for the alternative food as the prevention of degenerative disease and can be used as a snack food on children because the cost of making is classified as cheap and can contribute to carotene and crude fiber. Keywords : steamed sponge cake, purple sweet potato, seaweed flour, glycemic index